Qualidade da água, modos de vida ribeirinho e saneamento na Amazônia Marajoara: um percurso interdisciplinar - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Access to water is a legal right, as is access to basic sanitation, which gives people dignity and quality of life. In the Amazon, there are municipalities with geographical features that make it difficult to implement sanitation measures. The aim of this study is therefore to analyze, from an interdisciplinary perspective, how water quality, riverside lifestyles and sanitation can contribute to the promotion of social public policies in the Amazon. This consolidated study consists of three studies with independent methodologies that are interrelated, so that the first chapter uses bibliographical, documentary and scientometric research on scientific research into water quality in the Brazilian Amazon from 2000 to 2022 in the Web of Science and Scopus databases; the second chapter uses non-participant observation and photographs during the stay in the Itatupã-Baquiá Sustainable Development Reserve in Gurupá-PA and its investigation into ways of life in the face of existing public policies; and the third chapter uses documentary research with a descriptive analysis of the Implementation of the Basic Sanitation Policy in the Municipality of Gurupá-PA. As for the results, the first analysis showed that interdisciplinarity is a significant factor in the studies carried out in the context of water quality in the Amazon, because of the 95 articles filtered, it was possible to identify the main aspects of research developed in the region, mainly through the development of the Institute of Coastal Studies of the Federal University of Pará in the municipality of Bragança and its leadership in scientific development in the northern region on the theme of sustainability, biodiversity conservation and emerging themes such as the presence of pathogens of human risk in the region's waters; the second study made it possible to detect the adaptation of riverside lifestyles in the face of the human-nature relationship within a Sustainable Development Reserve and the almost non-existent presence of public authorities through the stimulation of public policies, including sanitation, education and health, where the population seeks to organize itself to improve its conditions. With emphasis on sanitation, the municipality has a deficit in the implementation of actions, both in terms of planning and the lack of accountability through public management instruments. Thus, we conclude that the constant of water and its correlation to the riverside way of life and its interdependence with regard to public policies, including sanitation, where by analyzing the data regarding the service in the municipality of Gurupá, we identify problems that permeate social and political aspects that allow for the viability of dignified access to sanitation, with measures being adopted from an economically viable and socially sustainable perspective.
Keywords: Acesso a água; Sustentabilidade; Política pública; Direito social; Saúde ambiental; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS